Trends in forced displacement due to conflict from 2009 to 2021: A decade forecast for effective humanitarian emergency response system in Nigeria - Izuakor, Chidubem Fidelis (Frontiers in Human Dynamics, 2022)
Internal displacement figures in conflicted affected regions of Nigeria is a significant problem that poses a risk of humanitarian crises accounted for by poor and a neglected emergency response system. The present study analyzed annual conflict/violence-induced internal displacement trends in Nigeria from 2009 to 2021 and predicted the annual figures for the next 10 years. Using the R software, the Autoregressive Integrated Moving Average (ARIMA) was adopted for analysis, while model (0, 0, 1) was chosen as the best fitting model with the minimum AIC coefficient. From the ARIMA forecast, 2022 showed a 4% decrease in displacement figures, further decreasing by 7% in 2023. The figures remained constant for the rest of the forecasted years, showing neither increases nor decreases from 2024 to 2031. Close observation revealed the overlapping trends between increased annual internal displacements and pre-election periods in Nigeria. This study will help inform humanitarian bodies on the significance of early detection and preparation for future displacement crises while considering the cycle of ethno-religious-related electoral violence. Furthermore, future studies should compare the accuracy of ARIMA with other models to ensure its validity using a similar sample.